El control de inversiones en la UE y los EE.UU. Diferentes modelos - ¿Los mismos objetivos? - Arp, Björn (2023)
This article analyzes the control of foreign investments carried out in recent years by the US and the European Union (EU). This analysis is justified because for only about five or six years on both sides of the Atlantic, the control of investments that reach these territories has been strengthened. The article clarifies and compares the scope of investment control in each of these two territories. This study allows us to observe the risks of a progressive expansion of the notion of “national security”, and especially in the EU - due to the decentralized nature of investment control - to a political use with an impact on relations between Member States and EU bodies, including the judicialization of the definition of national security and public order through the intervention of the Court of Justice of the EU. In addition, investment screening may impact the EU-US trade and investment relations.